2016
DOI: 10.26719/2016.22.11.778
|View full text |Cite
|
Sign up to set email alerts
|

Trends in infectious disease incidence among children in Afghanistan at a time of public health services expansion

Abstract: This study reviewed trends in the incidence of common communicable diseases among children under five years in Afghanistan between 2005 and 2013, a period of expansion of public health services. New visits to outpatient clinics constituted the denominator for calculating proportions. In 2013, almost three-quarters of all new visits of children to public health services were for an infectious disease, with respiratory infections the most common. Because of inconsistent data collection for some infections early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In four studies looking at pneumonia in outpatient settings , pneumonia represented 12%-34% of diagnoses for children U5 [ 17 , 19 - 21 ]. No studies included older children or adolescents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In four studies looking at pneumonia in outpatient settings , pneumonia represented 12%-34% of diagnoses for children U5 [ 17 , 19 - 21 ]. No studies included older children or adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…Nationally representative data from conflict-affected Afghanistan showed that pneumonia cases decreased as a proportion of U5 admissions from 12.2% to 8.6% between 2005 and 2013 [ 19 ]. However, Bernasconi et al’s study of children attending primary care facilities in Kabul, Afghanistan, revealed significant under-recognition of pneumonia by health care workers finding that pneumonia represented 9.7% (39/404) of U5 presentation at baseline but 21.2% (141/665) of presentations after introduction of an electronic decision-making tool that encouraged adherence to IMCI guidelines [ 21 ].…”
Section: Resultsmentioning
confidence: 99%